2018
DOI: 10.3892/or.2018.6276
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of EPCR inhibits the proliferation and migration of human gastric cancer cells via the ERK1/2 pathway in a PAR-1-dependent manner

Abstract: Endothelial protein C receptor (EPCR) has been implicated in the carcinogenesis of diverse tumor types. This tumor-promoting effect of EPCR is associated with the upregulation of activated protein C and the activation of protease-activated receptor 1 (PAR-1). However, the exact role of EPCR in gastric cancer (GC) and the mechanisms underlying the regulation of EPCR remain elusive. In the present study, we investigated the effects of EPCR on human GC cells, as well as the underlying mechanisms. An siRNA inferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Furthermore, CRISPR knockout of EPCR reduces human trophoblast proliferation and invasion, 46 and siRNA knockdown of EPCR in human gastric cancer cells inhibits proliferation and migration. 47 3K3A-APC also increased activation of MMP-2 in mouse fibroblasts, as previously demonstrated by APC In human fibroblasts. 12 That it did so in both phenotypes may be explained by our previous finding that APC can directly activate MMP-2 even in the absence of cells, 32 suggesting 3K3A-APC similarly activates MMP-2 suspended in media without the need for surface membrane proteins such as EPCR.…”
Section: Mouse Studiessupporting
confidence: 84%
“…Furthermore, CRISPR knockout of EPCR reduces human trophoblast proliferation and invasion, 46 and siRNA knockdown of EPCR in human gastric cancer cells inhibits proliferation and migration. 47 3K3A-APC also increased activation of MMP-2 in mouse fibroblasts, as previously demonstrated by APC In human fibroblasts. 12 That it did so in both phenotypes may be explained by our previous finding that APC can directly activate MMP-2 even in the absence of cells, 32 suggesting 3K3A-APC similarly activates MMP-2 suspended in media without the need for surface membrane proteins such as EPCR.…”
Section: Mouse Studiessupporting
confidence: 84%
“…The localization of prothrombin and PAR1 in GC suggests that these factors may be important mediators of cellular function in the ovarian follicle (Roach et al, 2002). Similarly, it has been reported that in human gastric cancer cells, in vitro knockdown of EPCR inhibits cell proliferation and migration by inhibiting the activation of PAR1 and MAPK3/1 (Q. Wang et al, 2018). Also, EPCR knockdown or treatment with PAR1 antibody significantly decreased MAPK3/1 phosphorylation (Q. Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, it has been reported that in human gastric cancer cells, in vitro knockdown of EPCR inhibits cell proliferation and migration by inhibiting the activation of PAR1 and MAPK3/1 (Q. Wang et al, 2018). Also, EPCR knockdown or treatment with PAR1 antibody significantly decreased MAPK3/1 phosphorylation (Q. Wang et al, 2018). In ovalbumin‐allergic rats, thrombin promotes airway remodeling via PAR1, while MAPK3/1 signaling pathway plays an important role in this process since pMAPK3/1 inhibitors effectively inhibit the airway remodeling in these rats (Bi et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…There are contradictory findings that are of paramount importance with respect to the role of the APC/EPCR/PAR-1 axis in cancer progression [42,75,76]. Wang et al [42] demonstrated that gastric cancer tissue expresses elevated levels of EPCR and that EPCR-mediated APC activation induces proliferation and migration of the MGC803 gastric cancer cells.…”
Section: Epcr and Par-1 Interactionsmentioning
confidence: 99%